Reflections of future Mathematics teachers on Financial Education: perspectives for Basic Education - Cantareira, Ana Beatriz Paiva; Hartmann, Andrei Luís Berres; Malheiros, Ana Paula dos Santos (Educação Matemática Debate, 2024)
Since the publication of the Base Nacional Comum Curricular (National Common Curricular Base), Financial Education has become a topic to be developed in the classroom, mainly related to the mathematics curriculum. In this sense, teachers are in charge of addressing it. In view of this, in this paper we aim to discuss understandings of Financial Education aimed at Basic Education and produced by mathematics undergraduates, mobilized in two training meetings. Based on Critical Mathematics Education and the qualitative research paradigm, we identified five topics using content analysis procedures. The results of the analysis of these topics indicate that the future teachers have knowledge of School Financial Education, although they relate the subject to economic aspects and Financial Mathematics.